Analyzing the role of BRAC Bank PLC in promoting economic empowerment and financial inclusion (FI) among low-income individuals - Sheila, Nabuduwa (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.